PEMBANGUNAN HUKUM KETENAGAKERJAAN DI INDONESIA SUATU KAJIAN TERHADAP PENGATURAN DAN PERLINDUNGAN HUKUM BAGI PEKERJA KONTRAK/OUTSOURCHING) - Indra Muchlis Adnan; wandi (Fakultas Hukum Universitas Islam Indragiri, 2017)
Providing legal protection for workers / laborers constitute the mandate and objectives of the labor laws to achieve or implement social justice in the field of labor and employment protects against the unlimited power of entrepreneurs. Legal safeguards for workers / laborers outsourcing should be implemented to the fullest and, more specifically, given the practice of outsourcing occurs triangular employment relationships involving corporate employer (principal) the recipient company jobs (vendors) and workers / laborers.